A Study on the Effect of the Boron Potential on the Mechanical Properties of the Borided Layers Obtained by Boron Diffusion at the Surface of AISI 316L Steel - E. Hernández-Sánchez; Y. M. Domínguez-Galicia; C. Orozco-Álvarez; R. Carrera-Espinoza; H. Herrera-Hernández; J. C. Velázquez (Advances in Materials Science and Engineering)
The effect of the boron potential on the thickness and the mechanical properties of borided layers was evaluated. The boron potential was established by means of the available atoms of boron contained in a control volume inside a cylinder. The cylinders were manufactured from AISI 316L steel, and the boriding treatment was performed using the powder pack technique at a temperature of 1273 K over an exposure time of 6 h. Four different internal diameters of the cylinders were evaluated (3.17, 4.76, 6.35, and 7.93 mm). The mechanical properties were evaluated using the Berkovich instrumented indentation technique. The results showed a clear influence of the boron potential on the mechanical properties of the layers. The hardness of the layers was stablished in the range of 16.22 to 21.16 GPa. Young’s modulus values were stablished in the range of 255.96 to 341.37 GPa. Also the fracture toughness and brittleness of the layers reflected the influence of the boron potential supplied during the boriding process. Finally, the influence of the boron potential on the constant of parabolic growth (K) was also established as a function of the inner diameter of the cylinders.